Peningkatan Literasi Geografi dan Kesadaran Mitigasi Bencana bagi Siswa Sekolah Menengah di Daerah Rawan Tsunami - Rosely, Merti Seska; Manakane, Susan Evelin; Partini, Dwi (Universitas Pattimura, 2025)
This community service program was implemented in the coastal area of Ambon City, which is highly vulnerable to tsunamis and coastal abrasion. It was motivated by the low level of geographical literacy and disaster awareness among high school students. The aim was to enhance spatial understanding and disaster preparedness through a participatory approach combining local mapping, simple geospatial technology, and local wisdom. The method employed a Participatory Action Research model consisting of problem identification, teacher-student training, participatory mapping, mitigation simulation, and impact evaluation. The results indicated a significant improvement in students’ ability to interpret risk maps and evacuation routes, as well as the creation of locally contextualized mitigation learning modules. This program contributes both conceptually and practically to strengthening disaster education in coastal schools and encourages replication in other regions with supportive policies and simple technologies